HUBUNGAN INDEKS MASSA TUBUH DENGAN PROGRESIVITAS MIOPIA PADA ANAK SEKOLAH MENENGAH PERTAMA DI DAERAH ISTIMEWA YOGYAKARTA - , RIZKIKA BELLANI PERTIWI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Myopia is the most common refractive error in school - aged children. A research in America showed 1 in 10 children aged 5 â 17 years were reported to suffer from myopia. Nutritional factor is considered to have a role in myopia development. A study reported that body mass index increased in patient with myopia (Lazarus et al, 2000). Purpose: to determine whether there is a relationship between body mass index and progression of myopia. Methods: The study design was prospective observational cohort type. This research was conducted in five junior high schools in Yogyakarta , two of urban area (SMP Negeri 1 Kalasan and SMP Taman Siswa) and three of rural area (MTS Godean, SMP Muhammadiyah 1 Godean, and SMP Negeri 3 Pengasih). Follow-up examination performed within 6 months (June-December 2012). Results and conclusion: There was no significant relationship between body mass index and progression of myopia. SPSS analysis showed that the correlation between body mass index and progression of myopia was weak and negative or opposite direction (the higher the body mass index, the more the degree of myopia decreased).